Negative symptoms and social cognition as mediators of the relationship between neurocognition and functional outcome in schizophrenia - Giordano, Giulia M.; Pezzella, Pasquale; Mucci, Armida; Austin, Stephen F.; Erfurth, Andreas; Glenthøj, Birte; Hofer, Alex; Hubenak, Jan; Libiger, Jan; Melle, Ingrid; Nielsen, Mette Ø.; Rybakowski, Janusz K.; et al. (Frontiers in Psychiatry, 2024)
In this study we assessed the contribution of psychopathology, including the two domains of negative symptoms (motivational deficit and expressive deficit), processing speed as an index of neurocognition, and emotion recognition, as an index of social cognition, to poor functional outcomes in people with schizophrenia.The Positive and Negative Syndrome Scale was used to evaluate positive symptoms and disorganization and the Brief Negative Symptom Scale to assess negative symptoms. The Symbol Coding and the Trail Making Test A and B were used to rate processing speed and the Facial Emotion Identification Test to assess emotion recognition. Functional outcome was assessed with the Personal and Social Performance Scale (PSP). Regression analyses were performed to identify predictors of functional outcome. Mediation analyses was used to investigate whether social cognition and negative symptom domains fully or partially mediated the impact of processing speed on functional outcome.One hundred and fifty subjects from 8 different European centres were recruited. Our data showed that the expressive deficit predicted global functioning and together with motivational deficit fully mediated the effects of neurocognition on it. Motivational deficit was a predictor of personal and social functioning and fully mediated neurocognitive impairment effects on the same outcome.Both motivational deficit and neurocognitive impairment predicted socially useful activities, and the emotion recognition domain of social cognition partially mediated the impact of neurocognitive deficits on this outcome.Our results indicate that pathways to functional outcomes are specific for different domains of real-life functioning and that negative symptoms and social cognition mediate the impact of neurocognitive deficits on different domains of functioning. Our results suggest that both negative symptoms motivational deficits and social cognition should be targeted by psychosocial interventions to enhance the functional impact of neurocognitive remediation.